Between what users say and what they do: the most useful UX research methods in assessing website quality - Morales-Vargas, Alejandro (Anuario ThinkEPI, 2023)
Analysing user experience (UX) is a key factor in evaluating website quality. There are 20 methods for this purpose that, through qualitative or quantitative perspectives, examine people´s attitudes, behaviours or context of use. However, for different economic or practical reasons, this type of study is usually less utilized than heuristic evaluations. Therefore, this article details and recommends the most effective techniques in a prioritized manner. Web analytics -the tool that collects the largest amount of data- is in first place, followed by usability tests, observation and questionnaires. All of these have the aim of facilitating the listening to of users´ voices and finding out what it is they really do when on a website.